Design and development of a legged robot (I) - Tri Wira Efendi. (2009)
This final year project aims to design and develop an autonomous legged robot to compete in TechFest 2009 in India. An autonomous legged robot is built from the ground up with S$1,000 budget in 20 weeks. It must satisfy the size constrain (750x750x750mm), weight constraint (10kg), and rules of the competition. The task that needs to be performed by the legged robot is to walk through a U-shape track with some obstacles autonomously. The obstacles consist of 3cm step, 5cm step, 6cm step, 7 cm pipe obstacle, and two 90 degrees turn. The aim of the legged robot is to reach the finish line in shortest time period. The design uses the existing 6 legged robot in Mechatronics and Control Lab. The study of this existing design was performed to analyze the conformity with the TechFest rules. Some modifications were added into the existing design so that the robot will be able to perform in TechFest arena. The leg spacing was increased to allow wider leg swing and battery compartments and circuit platform were added into the basic design. The legged robot has 3 servo motors on each leg. With these 3 motors, the robot leg can be more flexible, hence it enhances the ability to clear the obstacles in the arena. The robot will be able to walk straight, rotate, and lift its body to clear the obstacle. In order to let the robot performs autonomously, sensors and microcontrollers are installed into the robot. Eight Basic Stamps 2SX and 6 QTI sensors are used in the robot, 1 BS to control the sensor, 1 BS for each leg, and 1 BS as the main brain to control the whole system. The 6 QTI sensors are utilized to provide line detection to allow the robot to be aware of its position in the arena. After 20 weeks, the legged robot was completed. Up to the point of this report, the robot has been able to perform a simple walking motion. However, due to some unforeseen problems, the walking motion of the robot was not smooth enough. With further development, the robot is expected to be able to perform well in the TechFest competition.